Theory Of Cognitive Development By Jean Piaget - Farida Hanum Pakpahan; Marice Saragih (Journal of Applied Linguistics, 2022)
Although many core themes and concepts unite the field of cognitive development, it is a wide and varied field, particularly when it comes to cognitive development in early. Piaget proposed four cognitive developmental stages for children, including sensorimotor, preoperational, concrete operational, and the formal operational stage. Although Piaget’s theories have had a great impact on developmental psychology, his notions have not been fully accepted without critique. Piaget’s theory has some shortcomings, including overestimating the ability of adolescence and underestimating infant’s capacity. Piaget also neglected cultural and social interaction factors in the development of children’s cognition and thinking ability. Cognitive development occurs at several stages during childhood. As a result, cognitive development studies the nature of child development in terms of how they gain conscious control over their intellect and behavior. Piaget contributions, particularly in regards to the process of education among children and transferring cognition into psychology, have had a significant effect on the science of child development. Keywords: Cognitive Development, Child Development